2016
DOI: 10.1111/ases.12310
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of transanal tube placement for prevention of anastomotic leakage following laparoscopic low anterior resection

Abstract: Transanal tube placement prevents AL after LLAR. Furthermore, this protective effect may be due to a reduction in the unfavorable incidence of early postoperative diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…Only one case (2.3%) was found to occur AL in this study. It was almost the same rate of the previous report of Dr. Sato [9] and was better than the report of Dr. Ito [6].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Only one case (2.3%) was found to occur AL in this study. It was almost the same rate of the previous report of Dr. Sato [9] and was better than the report of Dr. Ito [6].…”
Section: Discussionsupporting
confidence: 78%
“…Recently, after Laparoscopic Low Anterior Resection (LLAR) AL occurred 12.3% among 154 patients [5]. To prevent AL after LLAR, Tetsuo Ito reported the usefulness of transanal tube [6]. They reported that AL rate was 3.6% in 28 patients with tube in comparison with 24.4% without tube replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative diarrhea: Ito et al[ 44 ] reported an association between postoperative diarrhea and occurrence of AL, with an OR of 86.3. The authors speculated that early postoperative diarrhea increases endoluminal pressure at the anastomotic site.…”
Section: Risk Factors For Leakagementioning
confidence: 99%
“…Diverting stoma: Although evidence regarding the clinical benefit of fecal diversion is conflicting, it is generally agreed that creation of a diverting stoma (DS) can reduce the clinically adverse effects of AL, including fecal peritonitis and septicemia, rather than preventing leakage. In a retrospective series of 69 patients undergoing LAR[ 44 ], no significant difference between DS group and no-DS group in terms of AL incidence (15.4% vs 16.3%) was noted. Although AL was observed in four patients in the DS group, none of them developed AL grade C. In contrast, 57.1% (4/7 cases) of the patients in the no-DS group developed AL grade C, but this difference did not reach statistical significance[ 44 ].…”
Section: Risk Factors For Leakagementioning
confidence: 99%
“…No deaths occurred in the DS group, and the reoperation rate decreased when anastomotic leakage occurred, although this was not statistically significant. It is generally believed that a DS may reduce the clinically adverse effects of anastomotic leakage, such as peritonitis and sepsis, rather than prevent leakage (29).…”
Section: Discussionmentioning
confidence: 99%